Nonaqueous electrolyte power storage element
By using silicon-based living substances and α-NaFeO2 as the positive electrode active substances in the nonaqueous electrolyte energy storage equipment, and adding sulfur-containing cyclic compounds and fluorinated cyclic carbonate to the electrolyte, the problems of nonaqueous electrolyte decomposition and large gas generation caused by the lithium metal negative electrode active substances during the charge and discharge cycle are solved, and high energy density and good capacity retention rate are achieved.
Patent Information
- Application Number
- JP2023179621
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-18
- Publication Date
- 2025-05-01
AI Technical Summary
When existing non-aqueous electrolyte energy storage equipment uses lithium metal as the negative electrode, the continuous decomposition of non-aqueous electrolytes and the gas generation amount during the charge and discharge cycle, resulting in a decrease in energy density and capacity retention.
The lithium-transfer metal composite oxide with a high theoretical capacity is used as the negative electrode living agent, and α-NaFeO2 is used as the main component in the positive electrode living agent layer, and the sulfur-containing cyclic compound and fluorinated cyclic carbonate are combined as components of the non-aqueous electrolyte to control its content in the electrolyte.
The energy density of energy storage equipment is improved, the amount of gas generated during the charge and discharge cycle is reduced, and the capacity retention rate is enhanced.
Smart Images

Figure 2025069724000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a non-aqueous electrolyte electricity storage element. [Background technology]
[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. Non-aqueous electrolyte secondary batteries generally have a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring charge-transporting ions between the electrodes. In addition, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used as non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries.
[0003] Conventionally, the positive electrode active materials used in non-aqueous electrolyte storage elements are LiCoO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 Lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, such as α-NaFeO2, have been studied and put to practical use (see Patent Document 1). On the other hand, nonaqueous electrolyte electricity storage elements using a silicon-based active material (active material containing silicon element) as the negative electrode active material are known (see Patent Documents 2 to 4). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2015-018678 A [Patent Document 2] JP 2015-053152 A [Patent Document 3] JP 2010-212228 A [Patent Document 4] JP 2004-356078 A Summary of the Invention [Problem to be solved by the invention]
[0005] In non-aqueous electrolyte storage elements, a higher energy density is desired. To this end, it is considered to use metallic lithium, which has a large theoretical capacity per mass, as the negative electrode active material. However, in the case of a non-aqueous electrolyte storage element using metallic lithium as the negative electrode active material, the non-aqueous electrolyte is likely to continuously decompose with charge / discharge cycles, and a large amount of gas is generated. If the amount of gas in the non-aqueous electrolyte storage element increases with charge / discharge cycles, it causes a decrease in the discharge capacity retention rate.
[0006] An object of the present invention is to provide a nonaqueous electrolyte electricity storage element which has a high energy density per mass and which is suppressed in gas generation and decrease in discharge capacity retention rate due to charge / discharge cycles. [Means for solving the problem]
[0007] A nonaqueous electrolyte storage element according to one aspect of the present invention comprises a positive electrode having a positive electrode active material layer, a negative electrode having a negative electrode active material layer, and a nonaqueous electrolyte having a nonaqueous solvent and a cyclic compound containing elemental sulfur, the positive electrode active material layer being mainly composed of a lithium transition metal composite oxide having an α-NaFeO2 type crystal structure, and the positive electrode active material layer having a mass per area of 3.5 g / 100 cm 2 More than 10.5g / 100cm 2 the negative electrode has elemental sulfur on at least a portion of its surface, the negative electrode active material layer is mainly composed of a silicon-based active material, the content of the cyclic compound containing the elemental sulfur in the non-aqueous electrolyte is 18 mass % or less, the non-aqueous solvent contains a fluorinated cyclic carbonate and a fluorinated chain solvent, and the content of the fluorinated cyclic carbonate in the non-aqueous solvent is 20 volume % or more. Effect of the Invention
[0008] According to one aspect of the present invention, it is possible to provide a nonaqueous electrolyte electricity storage element that has a high energy density per mass and is suppressed in gas generation and decrease in discharge capacity retention rate due to charge / discharge cycles. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a perspective view showing one embodiment of a nonaqueous electrolyte electricity storage element. [Diagram 2] FIG. 2 is a schematic diagram showing one embodiment of an electricity storage device formed by assembling a plurality of nonaqueous electrolyte electricity storage elements. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] First, an overview of the nonaqueous electrolyte electricity storage element disclosed in this specification will be described.
[0011] [1] A nonaqueous electrolyte storage element according to one aspect of the present invention comprises a positive electrode having a positive electrode active material layer, a negative electrode having a negative electrode active material layer, and a nonaqueous electrolyte having a nonaqueous solvent and a cyclic compound containing elemental sulfur, the positive electrode active material layer being mainly composed of a lithium transition metal composite oxide having an α-NaFeO2-type crystal structure, and the positive electrode active material layer having a mass per area of 3.5 g / 100 cm 2 More than 10.5g / 100cm 2 the negative electrode has elemental sulfur on at least a portion of its surface, the negative electrode active material layer is mainly composed of a silicon-based active material, the content of the cyclic compound containing the elemental sulfur in the non-aqueous electrolyte is 18 mass % or less, the non-aqueous solvent contains a fluorinated cyclic carbonate and a fluorinated chain solvent, and the content of the fluorinated cyclic carbonate in the non-aqueous solvent is 20 volume % or more.
[0012] The nonaqueous electrolyte storage element described in [1] above has a high energy density per mass, and suppresses gas generation and a decrease in the discharge capacity retention rate associated with charge / discharge cycles. The reason for this is unclear, but the following reason is presumed. The silicon-based active material, which is the negative electrode active material used as the main component in the nonaqueous electrolyte storage element described in [1] above, has a larger theoretical capacity per mass than carbon materials such as graphite, so the nonaqueous electrolyte storage element described in [1] above has a high energy density per mass. Note that the theoretical capacity per mass of the silicon-based active material is smaller than the theoretical capacity per mass of metallic lithium. However, in a non-aqueous electrolyte storage element using a silicon-based active material as the main component for the negative electrode active material, by increasing the mass per area of the positive electrode active material layer mainly composed of a lithium transition metal composite oxide having an α-NaFeO2 crystal structure, the opposing area of the positive electrode active material layer and the negative electrode active material layer required to obtain the same amount of energy can be reduced, and the mass of the positive electrode (e.g., positive electrode substrate) and the like can be reduced, resulting in an increase in the energy density per mass of the non-aqueous electrolyte storage element. On the other hand, if the mass per area of the positive electrode active material layer is too large, polarization due to the diffusion resistance of charge transport ions (lithium ions, etc.) in the thickness direction of the positive electrode active material layer and local disconnection of the electronic conduction path and the ionic conduction path are likely to occur, and the energy density per mass of the non-aqueous electrolyte storage element tends to decrease conversely. In the non-aqueous electrolyte storage element described in [1] above, the mass per area of the positive electrode active material layer mainly composed of a lithium transition metal composite oxide having an α-NaFeO2 crystal structure is 3.5 g / 100 cm. 2 More than 10.5g / 100cm 2The energy density per mass is high because the above ratio is 0.01 to 0.01. In addition, when metallic lithium is used as the negative electrode active material, the surface area of metallic lithium increases due to the dissolution and precipitation reaction of metallic lithium, and a new surface is always formed, so that the contact area between the non-aqueous electrolyte and metallic lithium increases with charge and discharge cycles. Therefore, when metallic lithium is used as the negative electrode active material, continuous decomposition of the non-aqueous electrolyte accompanying the charge and discharge cycles is promoted, and the amount of gas generated increases. In contrast, silicon-based active materials utilize alloying reactions for charging and discharging. Therefore, when a silicon-based active material is used as the negative electrode active material, the contact area between the non-aqueous electrolyte and the silicon-based active material accompanying the charge and discharge cycles is unlikely to increase, and the amount of gas generated is small. In addition, in a non-aqueous electrolyte storage element using a silicon-based active material, the capacity retention rate after charge-discharge cycles is increased by including 20% by volume or more of a fluorinated cyclic carbonate in the non-aqueous solvent of the non-aqueous electrolyte. This is believed to be due to the formation of a suitable coating derived from the fluorinated cyclic carbonate on the surface of the silicon-based active material. However, when a fluorinated cyclic carbonate is simply used, the coating formation reaction caused by the decomposition of the fluorinated cyclic carbonate continues during the charge-discharge cycle, and gas is generated as a by-product at that time, and the volume of the non-aqueous electrolyte storage element increases significantly. In contrast, in the case of a non-aqueous electrolyte in which a cyclic compound containing a sulfur element is further added to a non-aqueous solvent containing a fluorinated cyclic carbonate and a fluorinated chain solvent so that the content is 18% by mass or less, both the cyclic compound containing a sulfur element and the fluorinated cyclic carbonate are involved in forming a coating on the surface of the silicon-based active material, so that the negative electrode has a sulfur element on at least a part of the surface, and the generation of gas as a by-product is suppressed. Furthermore, since the film-forming reaction involving both the cyclic compound containing elemental sulfur and the fluorinated chain solvent is difficult to proceed, the film-forming reaction involving both the cyclic compound containing elemental sulfur and the fluorinated cyclic carbonate proceeds preferentially, thereby suppressing gas generation. On the other hand, in the case of a non-aqueous electrolyte in which a cyclic compound containing a sulfur element is further added to a non-aqueous solvent that is a combination of a fluorinated cyclic carbonate and a solvent other than a fluorinated chain solvent, a film-forming reaction involving both the cyclic compound containing a sulfur element and the other solvent also proceeds, and the cyclic compound containing a sulfur element is consumed. As a result, the film-forming reaction involving both the cyclic compound containing a sulfur element and the fluorinated cyclic carbonate is inhibited, and the decomposition reaction of the fluorinated cyclic carbonate proceeds, so that gas generation is not sufficiently suppressed. In addition, it is considered that the film formed by the involvement of both the cyclic compound containing a sulfur element and the other solvent is not of good quality and cannot sufficiently protect the surface of the silicon-based active material. Therefore, when a large amount of a cyclic compound containing a sulfur element is contained in a non-aqueous solvent that contains a solvent other than a fluorinated chain solvent, the decrease in the capacity retention rate after charge-discharge cycles cannot be sufficiently suppressed. Furthermore, in the case of a non-aqueous electrolyte in which a cyclic compound containing a sulfur element is added to a non-aqueous solvent consisting of only a fluorinated cyclic carbonate, the decomposition of the fluorinated cyclic carbonate cannot be sufficiently suppressed because a large amount of the fluorinated cyclic carbonate is present. In addition, in the case of a non-aqueous solvent consisting of only a fluorinated cyclic carbonate, the viscosity of the non-aqueous electrolyte becomes high, and it may be difficult to exhibit good charge / discharge performance. For the reasons described above, it is presumed that the nonaqueous electrolyte storage element described in [1] above has a high energy density per mass and a high capacity retention rate after charge-discharge cycles, and also has a reduced amount of gas generated during charge-discharge cycles.
[0013] "Main component" refers to the component that is contained in the greatest amount by mass. Mass per area of the positive electrode active material layer (g / 100cm 2 ) is the area of the positive electrode active material layer (100 cm 2The area of the positive electrode active material layer refers to the area of one of a pair of opposing main surfaces (front and back) of one positive electrode active material layer. That is, for example, when the positive electrode active material layer is provided by coating, the area of the positive electrode active material layer is equal to the area where the positive electrode active material layer is coated. When the positive electrode active material layer is provided on both sides of the positive electrode substrate, the area and mass of the positive electrode active material layer are the area and mass of one of the positive electrode active material layers. The area and mass of the negative electrode active material layer described later are also defined in the same way as the area and mass of the positive electrode active material layer. For example, when the positive electrode active material layer is provided on both sides of the positive electrode substrate with a thickness of 10.0 g / 100 cm, respectively, 2 When the coating amount (solid content equivalent) is 10.0 g / 100 cm, the "mass per area of the positive electrode active material layer" is 10.0 g / 100 cm. 2 The positive electrode active material layer is 10.0 g / 100 cm on one side of the positive electrode substrate. 2 Even if the coating amount (solid content equivalent) is 10.0 g / 100 cm, the "mass per area of the positive electrode active material layer" is 10.0 g / 100 cm. 2 That is, in the case of a positive electrode active material layer provided on one or both sides of a positive electrode substrate, the "mass per area of the positive electrode active material layer" is the mass per area of the positive electrode active material layer per one side. The "mass per area of the negative electrode active material layer" described later is also defined in the same manner as the "mass per area of the positive electrode active material layer". The lithium transition metal composite oxide is confirmed to have an α-NaFeO2 type crystal structure by X-ray diffraction measurement. X-ray diffraction measurement of the lithium transition metal composite oxide is performed before charging and discharging, or on the lithium transition metal composite oxide that has been fully discharged by the following method. First, the nonaqueous electrolyte storage element is discharged at a constant current of 0.05C to the lower limit voltage for normal use. The nonaqueous electrolyte storage element in this state is disassembled, the positive electrode is removed, and a half cell is assembled with metallic lithium as the counter electrode. The positive electrode potential is measured at a discharge current of 10mA per 1g of positive electrode active material until the positive electrode potential reaches 2.0V vs.Li / Li. +The positive electrode is adjusted to a fully discharged state by constant current discharge until the positive electrode is fully discharged. The positive electrode is disassembled again and the positive electrode is taken out. Dimethyl carbonate is used to thoroughly wash off the components (non-aqueous electrolyte, etc.) attached to the taken-out positive electrode, and the positive electrode is dried under reduced pressure at room temperature for 24 hours, after which the lithium transition metal composite oxide of the positive electrode active material is taken out. X-ray diffraction measurement is performed by powder X-ray diffraction measurement using an X-ray diffractometer (Rigaku's "MiniFlex II") with a CuKα radiation source, a tube voltage of 30 kV, and a tube current of 15 mA. At this time, the diffracted X-ray passes through a Kβ filter with a thickness of 30 μm and is detected by a high-speed one-dimensional detector (D / teX Ultra 2). The sampling width is 0.02°, the scan speed is 5° / min, the divergence slit width is 0.625°, the receiving slit width is 13 mm (OPEN), and the scattering slit width is 8 mm.
[0014] The presence of sulfur element on at least a part of the surface of the negative electrode is confirmed by energy dispersive X-ray spectroscopy (EDX). The negative electrode is removed from the nonaqueous electrolyte storage element disassembled by the above procedure. The components (nonaqueous electrolyte, etc.) attached to the removed negative electrode are thoroughly washed using dimethyl carbonate, and the electrode is dried under reduced pressure at room temperature for 24 hours, and then subjected to EDX analysis. A TM3030Plus Miniscope (manufactured by Hitachi High-Technologies Corporation) is used for the EDX analysis. The EDX analysis conditions are an acceleration voltage of 15 kV, an accumulation number of 8 or more, and an X-ray count of 4 kcps or more. The peak at 2.309 keV in the EDX pattern is used to quantify the sulfur element.
[0015] The content of cyclic compounds containing sulfur element in the non-aqueous electrolyte is determined by gas chromatography-mass spectrometry (GC-MS). A 7890A GC system (Agilent Technologies) is used for gas chromatography-mass spectrometry (GC-MS). The non-aqueous electrolyte is extracted from the non-aqueous electrolyte storage element disassembled by the above procedure. The extracted non-aqueous electrolyte is appropriately diluted with acetone and subjected to analysis. The injection temperature is 240°C. An HP-5 column is used. The column is installed inside a temperature-controlled oven, and the temperature of the oven at the start of the measurement is 40°C. During the measurement, the temperature of the oven is increased to 90°C at 25°C / min, and further increased to 240°C at 15°C / min. An FID is used as the detector, and the temperature of the detector is 250°C. Helium gas is used as the carrier gas.
[0016] [2] In the nonaqueous electrolyte storage element according to the above [1], the positive electrode active material layer may have a porosity of 15% or more and 35% or less.
[0017] According to the nonaqueous electrolyte storage element described in [2] above, the energy density per unit mass can be increased. The reason for this is presumably that the porosity of the positive electrode active material layer is relatively low, so that the mass of the nonaqueous electrolyte filled in the pores of the positive electrode active material layer can be reduced, and local disconnection of the electron conduction path is less likely to occur. On the other hand, when the mass per area is 10.5 g / 100 cm 2 Conversely, when the porosity is relatively low in a positive electrode active material layer exceeding 100%, the energy density per mass tends to decrease. The reason for this is presumably that the reduction in the porosity of the positive electrode active material layer has a large effect on reducing the diffusion paths of charge transport ions (lithium ions, etc.) in the positive electrode active material layer.
[0018] The "porosity of the positive electrode active material layer" refers to a value calculated from the true density of the positive electrode active material layer calculated from the true density of each component constituting the positive electrode active material layer and the apparent density of the positive electrode active material layer by the following formula (1). Porosity (%) = 100 – (apparent density / true density) × 100 (1) The apparent density of the positive electrode active material layer is the value obtained by dividing the mass of the positive electrode active material layer by the apparent volume of the positive electrode active material layer. The apparent volume refers to the volume including the void portion (pore portion) and can be calculated as the product of the average thickness and the area of the positive electrode active material layer. The average thickness of the positive electrode active material layer is the average value of thicknesses measured at any five points.
[0019] [3] In the nonaqueous electrolyte storage element according to the above [1] or [2], the cyclic compound containing elemental sulfur may contain at least one selected from a compound having a cyclic sulfate structure and a cyclic sulfonate ester.
[0020] The inventors have found that, by forming a particularly good coating film with the involvement of both such a cyclic compound containing elemental sulfur and a fluorinated cyclic carbonate during charging and discharging, the decomposition of the fluorinated cyclic carbonate and the associated gas generation are further suppressed, and a similar coating formation reaction occurs in the case of a compound having a cyclic sulfate structure and in the case of a cyclic sulfonate ester, etc. Therefore, by using such a cyclic compound containing elemental sulfur, the nonaqueous electrolyte storage element described in the above [3] can further increase the capacity retention rate after charge-discharge cycles and further reduce the volume change.
[0021] [4] In the nonaqueous electrolyte storage element according to any one of the above [1] to [3], the cyclic compound containing elemental sulfur may have a sultone structure.
[0022] When a compound having a sultone structure is used, a particularly good coating film is formed, which further suppresses the decomposition of the fluorinated cyclic carbonate and the associated gas generation. Therefore, by using such a cyclic compound containing elemental sulfur, the nonaqueous electrolyte storage element described in [4] above can further reduce the volume change after charge-discharge cycles.
[0023] [5] In the nonaqueous electrolyte storage element according to any one of the above [1] to [4], the cyclic compound containing elemental sulfur may have a carbon-carbon double bond.
[0024] When a cyclic compound containing a sulfur element has a carbon-carbon double bond, the LUMO (Lowest Unoccupied Molecular Orbital) is calculated to be low, and it is considered that the compound is easily reductively decomposed at a high potential. Therefore, by using such a cyclic compound containing a sulfur element, a film-forming reaction involving both the cyclic compound and the fluorinated cyclic carbonate is easily generated before the fluorinated cyclic carbonate decomposes during charging, and gas generation due to the decomposition of the fluorinated cyclic carbonate is suppressed. Therefore, according to the nonaqueous electrolyte storage element described in [5] above, gas generation accompanying the charge-discharge cycle can be further suppressed.
[0025] A nonaqueous electrolyte electricity storage element, an electricity storage device, a method for manufacturing a nonaqueous electrolyte electricity storage element according to one embodiment of the present invention, and other embodiments will be described in detail. Note that the names of the components (elementary components) used in each embodiment may differ from the names of the components (elementary components) used in the background art.
[0026] <Non-aqueous electrolyte electricity storage element> A nonaqueous electrolyte storage element (hereinafter, simply referred to as "storage element") according to one embodiment of the present invention includes an electrode assembly having a positive electrode, a negative electrode, and a separator, a nonaqueous electrolyte, and a container that contains the electrode assembly and the nonaqueous electrolyte. The electrode assembly is usually a laminated type in which a plurality of positive electrodes and a plurality of negative electrodes are laminated with a separator interposed therebetween, or a wound type in which a positive electrode and a negative electrode are laminated with a separator interposed therebetween and wound. The nonaqueous electrolyte storage element according to one embodiment of the present invention preferably includes a laminated electrode assembly. In the case of a laminated electrode assembly, the porosity of the positive electrode active material layer can be made smaller, and therefore, there is an advantage that the energy density per mass of the nonaqueous electrolyte storage element can be increased. The container may be a known one such as a metal container or a resin container. From the viewpoint of increasing the energy density per mass of the nonaqueous electrolyte storage element, a container made of a film (such as a resin film or a metal-resin composite film) that is heat-sealed is also preferably used. The nonaqueous electrolyte is present in a state that it is contained in the positive electrode, the negative electrode, and the separator. As an example of the nonaqueous electrolyte storage element, a nonaqueous electrolyte secondary battery (hereinafter, simply referred to as a "secondary battery") will be described.
[0027] (positive electrode) The positive electrode has a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer.
[0028] The positive electrode substrate is conductive. Whether or not it has "conductivity" is determined by whether the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 -2The threshold value is Ω·cm. The material of the positive electrode substrate is a metal such as aluminum, titanium, tantalum, stainless steel, or an alloy thereof. Among these, aluminum or an aluminum alloy is preferred from the viewpoints of potential resistance, high conductivity, and cost. The positive electrode substrate may be a foil, a vapor deposition film, a mesh, a porous material, etc., and a foil is preferred from the viewpoint of cost. Therefore, aluminum foil or an aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or an aluminum alloy include A1085, A3003, A1N30, etc., as specified in JIS-H-4000 (2014) or JIS-H-4160 (2006).
[0029] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, even more preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate within the above range, it is possible to increase the strength of the positive electrode substrate and to increase the energy density per mass of the nonaqueous electrolyte storage element.
[0030] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer contains a conductive agent such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and may contain, for example, a binder and a conductive agent.
[0031] The positive electrode active material layer is mainly composed of a lithium transition metal composite oxide having an α-NaFeO2 type crystal structure. The lithium transition metal composite oxide is a positive electrode active material. The positive electrode active material layer may contain optional components such as a positive electrode active material other than the lithium transition metal composite oxide, a conductive agent, a binder, a thickener, and a filler, as necessary.
[0032] The lithium transition metal composite oxide having an α-NaFeO2 type crystal structure preferably contains at least one of nickel, cobalt and manganese, more preferably contains cobalt. The lithium transition metal composite oxide also preferably contains nickel and manganese, more preferably contains nickel, cobalt and manganese. By using such a lithium transition metal composite oxide, it is possible to further increase the energy density per mass of the non-aqueous electrolyte storage element. The lithium transition metal composite oxide may contain only cobalt as a transition metal element, may contain only nickel and manganese, or may contain only nickel, cobalt and manganese. The lithium transition metal composite oxide may further contain other metal elements such as aluminum.
[0033] The lower limit of the content of nickel element relative to the metal element other than lithium element in the lithium transition metal composite oxide may be 0.0, 0.1, 0.2, 0.3 or 0.4 in terms of a molar ratio when the content of metal element other than lithium element is 1.0. When the content of nickel element is relatively high, the energy density per mass of the nonaqueous electrolyte storage element tends to be higher. The upper limit of the content of nickel element may be 1.0, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, 0.1 or 0.0 in terms of a molar ratio when the content of metal element other than lithium element is 1.0. The content of nickel element may be any of the above lower limits or more and any of the above upper limits or less (however, the lower limit is the upper limit or less).
[0034] The lower limit of the content of the cobalt element relative to the metal element other than the lithium element in the lithium transition metal composite oxide may be 0.0, or 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1.0, in terms of a molar ratio when the content of the metal element other than the lithium element is taken as 1.0. The upper limit of the content of the cobalt element may be 1.0, or 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, 0.1, or 0.0, in terms of a molar ratio when the content of the metal element other than the lithium element is taken as 1.0. The content of the cobalt element may be any of the lower limits or more and any of the upper limits or less (however, the lower limit is any of the upper limits or less).
[0035] The lower limit of the content of elemental manganese relative to metal elements other than lithium element in the lithium transition metal composite oxide may be 0.0, or 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, or 1.0, in terms of a molar ratio when the content of metal elements other than lithium element is taken as 1.0. When the content of elemental manganese is relatively high, the capacity retention rate of the nonaqueous electrolyte storage element after charge-discharge cycles tends to be higher. The upper limit of the content of elemental manganese may be 1.0, or 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, 0.1, or 0.0, in terms of a molar ratio when the content of metal elements other than lithium element is taken as 1.0. The content of elemental manganese may be any of the above lower limits or more and any of the above upper limits or less (however, the lower limit is any of the above upper limits or less).
[0036] The total content of nickel, cobalt and manganese relative to the metal elements other than lithium in the lithium transition metal composite oxide is preferably 0.9 or more and 1.0 or less, and more preferably 0.99 or more and 1.00 or less, in terms of molar ratio, when the content of the metal elements other than lithium is taken as 1.0.
[0037] The lower limit of the content of lithium element relative to the metal elements other than lithium element in the lithium transition metal composite oxide may be 0.9, 1.0 or 1.05 in terms of a molar ratio when the content of metal elements other than lithium element is 1.0. The upper limit of the content of lithium element may be 1.6, 1.5, 1.4, 1.3 or 1.2 in terms of a molar ratio when the content of metal elements other than lithium element is 1.0. When the content of lithium element is equal to or less than the upper limit, the amount of gas generated during charge and discharge cycles tends to be reduced, and the discharge capacity of the positive electrode active material increases, so that the energy density per mass of the nonaqueous electrolyte storage element can be increased. The content of lithium element may be equal to or more than any of the lower limits and equal to or less than any of the upper limits.
[0038] The lithium transition metal composite oxide is preferably a compound represented by the following formula (2). Li 1+α M 1-α O2···(2) In formula (2), M is a metal element (excluding Li) containing at least one transition metal element, and 0≦α<1.
[0039] In formula (2), M preferably contains at least one of Ni, Co, and Mn, and more preferably contains Co. M more preferably contains Ni and Mn, and more preferably contains Ni, Co, and Mn. M may be Co alone, may consist of Ni and Mn, or may consist of Ni, Co, and Mn. M may further contain other metal elements such as Al.
[0040] In the above formula (2), the specific ranges of the molar ratio of Ni to M (Ni / M), the molar ratio of Co to M (Co / M), the molar ratio of Mn to M (Mn / M), the molar ratio of the total amount of Ni, Co, and Mn to M ((Ni+Co+Mn) / M), and the molar ratio of Li to M (Li / M) can be the same as the specific ranges of each metal element in the above-mentioned lithium transition metal composite oxide.
[0041] The composition ratio of the lithium transition metal composite oxide refers to the composition ratio before charging and discharging or when fully discharged by the following method. First, the nonaqueous electrolyte storage element is discharged at a constant current of 0.05 C to the lower limit voltage for normal use. The nonaqueous electrolyte storage element in this state is disassembled, the positive electrode is removed, and a half cell is assembled with metallic lithium as the counter electrode. The positive electrode potential is measured at a discharge current of 10 mA per 1 g of positive electrode active material until the positive electrode potential reaches 2.0 V vs. Li / Li. + The positive electrode is adjusted to a fully discharged state by constant current discharge until the positive electrode reaches a fully discharged state. The positive electrode is disassembled again and taken out. Dimethyl carbonate is used to thoroughly wash off the components (non-aqueous electrolyte, etc.) attached to the taken out positive electrode, and the positive electrode is dried under reduced pressure at room temperature for 24 hours, and then the lithium transition metal composite oxide of the positive electrode active material is taken out. Then, the lithium transition metal composite oxide taken out is completely dissolved using an acid capable of dissolving the metal elements contained in the lithium transition metal composite oxide by a microwave decomposition method. Next, this solution is diluted to a certain amount with pure water to obtain a measurement solution. Then, using a multi-type ICP optical emission spectrometer ICPE-9820 (manufactured by Shimadzu Corporation), the concentration of the metal elements in the measurement solution is measured by ICP optical emission spectroscopic analysis. The element content in the positive electrode active material is quantified from the obtained concentration of each element. In addition, in calculating the concentration of each element in the measurement solution, a calibration curve method can be used in which a calibration curve is created from a solution of each element with a known concentration, and the concentration of each element in the measurement solution is obtained. The operations from disassembling the nonaqueous electrolyte storage element to extracting the lithium transition metal composite oxide for measurement are carried out in an argon atmosphere with a dew point of −60° C. or lower. Here, normal use refers to the use of the nonaqueous electrolyte storage element under charge and discharge conditions recommended or specified for the nonaqueous electrolyte storage element.
[0042] The surface of the lithium transition metal composite oxide may be coated with another material, such as a compound containing an aluminum element, a tungsten element, a boron element, a zirconium element, or a niobium element.
[0043] The lithium transition metal composite oxide is usually a particle (powder). The average particle size of the lithium transition metal composite oxide is preferably, for example, 0.1 μm or more and 20 μm or less. The lower limit of the average particle size of the lithium transition metal composite oxide is preferably 1 μm or more, more preferably 4 μm or more, and even more preferably 8 μm or more. By setting the average particle size of the lithium transition metal composite oxide to the lower limit or more, the lithium transition metal composite oxide can be easily manufactured or handled, and the energy density per mass of the nonaqueous electrolyte storage element can be increased. By setting the average particle size of the lithium transition metal composite oxide to the upper limit or less, the electronic conductivity of the positive electrode active material layer is improved. In addition, when a composite of the lithium transition metal composite oxide and another material is used, the average particle size of the composite is set to the average particle size of the lithium transition metal composite oxide. "Average particle size" refers to the value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50%, based on the particle size distribution measured by laser diffraction / scattering method in accordance with JIS-Z-8825 (2013) for a solution obtained by diluting particles with a solvent.
[0044] In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, etc. are used. Examples of the pulverization method include a method using a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. During pulverization, wet pulverization in the presence of water or an organic solvent such as hexane can also be used. As a classification method, a sieve, an air classifier, etc. are used as necessary for both dry and wet methods.
[0045] The content of the lithium transition metal composite oxide in the positive electrode active material layer is preferably 60% by mass or more and 100% by mass or less, more preferably 80% by mass or more and 99.5% by mass or less, and even more preferably 90% by mass or more and 99% by mass or less. The content of the lithium transition metal composite oxide may be 95% by mass or more, 97% by mass or more, or 98% by mass or more. By setting the content of the lithium transition metal composite oxide in the above range, it is possible to achieve both high energy density per mass and manufacturability of the nonaqueous electrolyte storage element.
[0046] The positive electrode active material layer may further contain other positive electrode active materials other than the lithium transition metal composite oxide having an α-NaFeO2 type crystal structure. As the other positive electrode active materials, various conventionally known positive electrode active materials can be used. However, the content of the lithium transition metal composite oxide with respect to all the positive electrode active materials contained in the positive electrode active material layer is preferably 90 mass% or more, more preferably 99 mass% or more, and even more preferably 100 mass%. In this way, by mainly using the lithium transition metal composite oxide as the positive electrode active material, it is possible to increase the energy density per mass of the nonaqueous electrolyte storage element.
[0047] The content of all the positive electrode active materials in the positive electrode active material layer is preferably 60% by mass or more and 100% by mass or less, more preferably 80% by mass or more and 99.5% by mass or less, and even more preferably 90% by mass or more and 99% by mass or less. The content of all the positive electrode active materials may be 95% by mass or more, 97% by mass or more, or 98% by mass or more. By setting the content of all the positive electrode active materials within the above range, it is possible to achieve both high energy density per mass of the nonaqueous electrolyte storage element and manufacturability.
[0048] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, and the like. Examples of carbonaceous materials include graphite, non-graphitic carbon, graphene-based carbon, and the like. Examples of non-graphitic carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, and the like. Examples of the conductive agent include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. These materials may also be used in combination. For example, a material in which carbon black and CNT are combined may be used. Among these, carbon black and CNT are preferred from the viewpoint of electronic conductivity and coatability, and it is more preferred to use a mixture of acetylene black and CNT.
[0049] The content of the conductive agent in the positive electrode active material layer is preferably 0.1% by mass or more and 10% by mass or less, and more preferably 0.3% by mass or more and 9% by mass or less. The content of the conductive agent may be 5% by mass or less, 3% by mass or less, 2% by mass or less, or 1% by mass or less. By setting the content of the conductive agent in the above range, the energy density per mass of the nonaqueous electrolyte storage element can be increased.
[0050] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.
[0051] The content of the binder in the positive electrode active material layer is preferably 0.5% by mass or more and 10% by mass or less, more preferably 1% by mass or more and 9% by mass or less. The content of the binder may be 5% by mass or less, 3% by mass or less, or 2% by mass or less. By setting the content of the binder within the above range, the lithium transition metal composite oxide having an α-NaFeO2 type crystal structure and the like can be stably maintained.
[0052] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the thickener has a functional group that reacts with lithium or the like, the functional group may be deactivated in advance by methylation or the like. In one embodiment of the present invention, the positive electrode active material layer may not contain a thickener.
[0053] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, alumina, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and artificial products thereof. In one embodiment of the present invention, the positive electrode active material layer may not contain a filler.
[0054] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, I, etc., typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, etc., and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, W, etc., as components other than the lithium transition metal composite oxide having an α-NaFeO2 type crystal structure, other positive electrode active materials, conductive agents, binders, thickeners, and fillers.
[0055] The lower limit of the mass per area of the positive electrode active material layer is 3.5 g / 100 cm 2 and 4.0g / 100cm 2 is preferred, and 4.5g / 100cm 2 Or 5.0g / 100cm 2 On the other hand, the upper limit of the mass per area of the positive electrode active material layer is 10.5 g / 100 cm. 2 and 10.0g / 100cm 2 is preferable, and 9.0g / 100cm 2 Or 8.0g / 100cm 2 In some cases, it is more preferable that the mass per area of the positive electrode active material layer is within the above range. The energy density per mass of the nonaqueous electrolyte storage element can be increased. In order to facilitate handling during the manufacture of the positive electrode, the upper limit of the mass per area of the positive electrode active material layer is preferably 7.0 g / 100 cm. 2 is preferable, and 6.0g / 100cm 2 The mass per area of the positive electrode active material layer may be equal to or greater than any of the above-mentioned lower limits and equal to or less than any of the above-mentioned upper limits.
[0056] The upper limit of the porosity of the positive electrode active material layer is preferably 35%, more preferably 30%, further preferably 28%, and even more preferably 25%. The lower limit of the porosity of the positive electrode active material layer is preferably 15%, more preferably 18%, and further preferably 20%. By setting the porosity of the positive electrode active material layer within the above range, the energy density per mass of the nonaqueous electrolyte storage element can be further increased. The porosity of the positive electrode active material layer may be equal to or greater than any of the lower limits described above and equal to or less than any of the upper limits described above.
[0057] The porosity of the positive electrode active material layer can be adjusted by the average particle size of the lithium transition metal composite oxide, the contents of the components constituting the positive electrode active material layer, the strength of the press used when producing the positive electrode, and the like.
[0058] (Negative electrode) The negative electrode has a sulfur element on at least a part of its surface, and has a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The configuration of the intermediate layer is not particularly limited and can be selected from the configurations exemplified for the positive electrode.
[0059] The negative electrode substrate has electrical conductivity. Metals such as copper, nickel, stainless steel, nickel-plated steel, and aluminum, or alloys thereof, carbonaceous materials, etc. are used as the material of the negative electrode substrate. Among these, copper or copper alloys are preferred. Examples of the negative electrode substrate include foils, vapor deposition films, meshes, and porous materials, and foils are preferred from the viewpoint of cost. Therefore, copper foil or copper alloy foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil.
[0060] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, it is possible to increase the strength of the negative electrode substrate and to increase the energy density per mass of the nonaqueous electrolyte storage element.
[0061] The negative electrode active material layer is mainly composed of a silicon-based active material. The silicon-based active material is a negative electrode active material. The negative electrode active material layer contains optional components such as a negative electrode active material other than the silicon-based active material, a conductive agent, a binder, a thickener, and a filler, as necessary. The optional components such as a conductive agent, a binder, a thickener, and a filler can be selected from the materials exemplified for the positive electrode.
[0062] The negative electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W, as components other than the silicon-based active material, other negative electrode active materials, conductive agents, binders, thickeners, and fillers.
[0063] A silicon-based active material is an active material containing silicon element. Examples of the silicon-based active material include a simple substance of silicon element or a compound containing silicon element. Examples of the compound containing silicon element include silicon oxide (SiO x : 0 < x < 2, preferably 0.8 ≤ x ≤ 1.2), silicon nitride, silicon carbide, metal silicon compounds, etc. Examples of the metal silicon compound include compounds containing aluminum element, tin element, zinc element, nickel element, copper element, titanium element, vanadium element, magnesium element, etc. and silicon element. In addition, the silicon-based active material may be a composite material such as a SiO / Si / SiO2 composite material. As the silicon-based active material, those in which an element serving as a charge-transporting ion is pre-doped can also be used. That is, for example, the silicon-based active material may further contain lithium element. One kind or two or more kinds of the silicon-based active materials can be mixed and used. Among the silicon-based active materials, silicon oxide is preferred.
[0064] The silicon-based active material may have a surface coated with a conductive material such as a carbon material. By using the silicon-based active material in such a form, the electron conductivity of the negative electrode active material layer can be enhanced. When the silicon-based active material is in the form of particles or the like coated with a conductive material, the mass ratio of the conductive material to the total amount of the silicon-based active material and the conductive material coating it is, for example, preferably 1% by mass or more and 10% by mass or less, and more preferably 2% by mass or more and 5% by mass or less.
[0065] The silicon-based active material is usually particles (powder). The average particle size of the silicon-based active material can be, for example, 1 nm or more and 100 μm or less, and may be 1 μm or more and 30 μm or less, or may be 5 μm or more and 25 μm or less. By setting the average particle size of the silicon-based active material to be equal to or greater than the above lower limit, the production or handling of the silicon-based active material becomes easy. By setting the average particle size of the silicon-based active material to be equal to or less than the above upper limit, the electron conductivity of the negative electrode active material layer is improved. To obtain the silicon-based active material with a predetermined particle size, a pulverizer, a classifier, etc. are used. The pulverization method and the classification method can be selected, for example, from the methods exemplified for the positive electrode above.
[0066] The content of the silicon-based active material in the negative electrode active material layer is preferably 60% by mass to 99% by mass, more preferably 70% by mass to 98% by mass, and even more preferably 80% by mass to 97% by mass. The content of the silicon-based active material may be 85% by mass to 95% by mass, or 88% by mass to 92% by mass. By setting the content of the silicon-based active material within the above range, it is possible to achieve both high energy density per mass and manufacturability of the nonaqueous electrolyte storage element.
[0067] The negative electrode active material layer may further contain other negative electrode active materials than the silicon-based active material. As the other negative electrode active materials, various conventionally known negative electrode active materials such as carbon materials (graphite, non-graphitic carbon, etc.) can be used. However, the content of the silicon-based active material relative to all the negative electrode active materials contained in the negative electrode active material layer is preferably 90 mass% or more, more preferably 99 mass% or more, and even more preferably 100 mass%. In this way, by mainly using the silicon-based active material as the negative electrode active material, it is possible to increase the energy density per mass of the nonaqueous electrolyte storage element and to further reduce the generation of gas accompanying the charge / discharge cycle.
[0068] The content of all the negative electrode active materials in the negative electrode active material layer is preferably 60% by mass or more and 99% by mass or less, more preferably 70% by mass or more and 98% by mass or less, and even more preferably 80% by mass or more and 97% by mass or less. The content of all the above negative electrode active materials may be 85% by mass or more and 95% by mass or less, or 88% by mass or more and 92% by mass or less. By setting the content of all the negative electrode active materials within the above range, it is possible to achieve both high energy density per mass of the nonaqueous electrolyte storage element and manufacturability.
[0069] The conductive agent in the negative electrode active material layer may be the same as the conductive agent in the positive electrode active material layer. In the negative electrode active material layer, CNT may be used alone as the conductive agent.
[0070] The content of the conductive agent in the negative electrode active material layer is preferably 0.1% by mass or more and 10% by mass or less, and more preferably 0.3% by mass or more and 9% by mass or less. The content of the conductive agent may be 5% by mass or less, 3% by mass or less, 2% by mass or less, or 1% by mass or less. By setting the content of the conductive agent in the above range, the energy density per mass of the nonaqueous electrolyte storage element can be increased.
[0071] The binder content in the negative electrode active material layer is preferably 1% by mass to 15% by mass, more preferably 4% by mass to 10% by mass. By setting the binder content in the negative electrode active material layer within the above range, the silicon-based active material and the like can be stably held.
[0072] The content of the thickener in the negative electrode active material layer is preferably from 0.3% by mass to 4% by mass, and more preferably from 0.5% by mass to 2% by mass.
[0073] In one embodiment of the present invention, the negative electrode active material layer may not contain a filler.
[0074] The lower limit of the mass per area of the negative electrode active material layer is 0.5 g / 100 cm 2 is preferable, and 0.6g / 100cm 2 More preferably, 0.7 g / 100 cm 2 , 0.8g / 100cm 2 , 0.9g / 100cm 2 Or 1.0g / 100cm 2 On the other hand, the upper limit of the mass per area of the negative electrode active material layer is 2.0 g / 100 cm. 2 is preferred, and 1.8g / 100cm 2 More preferably, 1.7 g / 100 cm 2 , 1.6g / 100cm 2 , 1.4g / 100cm 2 , 1.2g / 100cm 2 Or 1.0g / 100cm 2is more preferable in some cases. By setting the mass per area of the negative electrode active material layer within the above range, the energy density per mass of the nonaqueous electrolyte storage element can be further increased. The mass per area of the negative electrode active material layer may be equal to or greater than any of the lower limits described above and equal to or less than any of the upper limits described above.
[0075] (Separator) The separator can be appropriately selected from known separators. For example, a separator consisting of only a base layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both sides of the base layer, etc. can be used as the separator. Examples of the shape of the base layer of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these shapes, a porous resin film is preferable from the viewpoint of strength, and a nonwoven fabric is preferable from the viewpoint of non-aqueous electrolyte retention. As the material of the base layer of the separator, polyolefins such as polyethylene and polypropylene are preferable from the viewpoint of shutdown function, and polyimide and aramid are preferable from the viewpoint of oxidation decomposition resistance. A material in which these resins are composited may be used as the base layer of the separator. The base layer may contain heat-resistant particles.
[0076] The heat-resistant particles contained in the heat-resistant layer or the base material layer preferably have a mass loss of 5% or less when heated from room temperature to 500°C under an air atmosphere at 1 atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800°C. Examples of materials with a mass loss of a predetermined amount or less include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; sparingly soluble ion crystals such as calcium fluoride, barium fluoride, and barium titanate; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and artificial products thereof. As the inorganic compound, these substances may be used alone or in the form of a complex, or two or more of them may be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of the safety of the nonaqueous electrolyte storage element.
[0077] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.
[0078] As the separator, a polymer gel composed of a polymer and a non-aqueous electrolyte may be used. Examples of the polymer include polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, and polyvinylidene fluoride. The use of the polymer gel has an effect of suppressing leakage. As the separator, the above-mentioned porous resin film or nonwoven fabric may be used in combination with the polymer gel.
[0079] (Non-aqueous electrolyte) The non-aqueous electrolyte contains an electrolyte salt, a non-aqueous solvent, and a cyclic compound containing elemental sulfur. Usually, the electrolyte salt and the cyclic compound containing elemental sulfur are dissolved in the non-aqueous solvent. Note that the cyclic compound containing elemental sulfur is not included in the non-aqueous solvent.
[0080] The electrolyte salt can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, onium salts, etc. Among these, lithium salts are preferred.
[0081] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2; lithium oxalate salts such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP); and lithium salts having halogenated hydrocarbon groups such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred. From the viewpoints of oxidation resistance and good film formation, the electrolyte salt is preferably one containing a fluorine element. As the electrolyte salt, LiPF6 is more preferred. One or more electrolyte salts can be used.
[0082] The lower limit of the electrolyte salt concentration in the non-aqueous electrolyte is 0.1 mol / dm at 20°C and 1 atmosphere. 3 , 0.3 mol / dm 3 , 0.5 mol / dm 3 or 0.7 mol / dm, but 0.9 mol / dm 3 is preferred, and 1.0 mol / dm 3 More preferably, 1.2 mol / dm 3 More preferably, 1.4 mol / dm 3When the concentration of the electrolyte salt in the nonaqueous electrolyte is equal to or higher than the lower limit, the volume change of the nonaqueous electrolyte storage element after charge-discharge cycles can be further reduced. The upper limit of the concentration of the electrolyte salt in the nonaqueous electrolyte is 2.5 mol / dm 3 is preferred, and 2.0 mol / dm 3 More preferably, 1.8 mol / dm 3 More preferably, 1.6 mol / dm 3 The concentration of the electrolyte salt in the non-aqueous electrolyte can be equal to or higher than any one of the above-mentioned lower limits and equal to or lower than any one of the above-mentioned upper limits.
[0083] The non-aqueous solvent includes a fluorinated cyclic carbonate and a fluorinated chain solvent. The fluorinated cyclic carbonate can form a good coating on the surface of the silicon-based active material, and also has high oxidation resistance. Therefore, the non-aqueous solvent contains a fluorinated cyclic carbonate, and is suitable as a non-aqueous electrolyte storage element in which a lithium transition metal composite oxide having an α-NaFeO2 crystal structure is used and the positive electrode reaches a high potential. In addition, the capacity retention rate after charge-discharge cycles can be increased in a non-aqueous electrolyte storage element having a negative electrode in which a silicon-based active material is used. On the other hand, the fluorinated chain solvent is a solvent in which a coating formation reaction involving both the cyclic compound containing a sulfur element does not easily proceed, and is also considered to have high oxidation resistance. Therefore, the non-aqueous solvent contains a fluorinated chain solvent, and does not inhibit the progress of the coating formation reaction involving both the cyclic compound containing a sulfur element and the fluorinated cyclic carbonate. Furthermore, when the non-aqueous solvent contains a fluorinated cyclic carbonate and a fluorinated chain solvent, the viscosity of the non-aqueous electrolyte is optimized, and the non-aqueous electrolyte storage element can exhibit good charge / discharge performance.
[0084] The fluorinated cyclic carbonate is a kind of cyclic solvent, and refers to a compound in which some or all of the hydrogen atoms of the cyclic carbonate are substituted with fluorine atoms. Examples of the fluorinated cyclic carbonate include fluorinated ethylene carbonate such as fluoroethylene carbonate (FEC) and difluoroethylene carbonate (DFEC), fluorinated propylene carbonate such as 3,3,3-trifluoropropylene carbonate, and fluorinated butylene carbonate. Among these, fluorinated ethylene carbonate is preferred, and FEC is more preferred. FEC has high oxidation resistance and can sufficiently increase the capacity retention rate after charge-discharge cycles in a nonaqueous electrolyte storage element. One or more fluorinated cyclic carbonates can be used.
[0085] The lower limit of the content of the fluorinated cyclic carbonate in the non-aqueous solvent is 20% by volume, preferably 22% by volume, more preferably 24% by volume, more preferably 26% by volume, even more preferably 28% by volume, and particularly preferably 30% by volume. By making the content of the fluorinated cyclic carbonate equal to or more than the above lower limit, the capacity retention rate after the charge-discharge cycle in the non-aqueous electrolyte storage element can be increased. The upper limit of the content of the fluorinated cyclic carbonate in the non-aqueous solvent is preferably 80% by volume, more preferably 60% by volume, more preferably 50% by volume, even more preferably 40% by volume, and particularly preferably 35% by volume. By making the content of the fluorinated cyclic carbonate equal to or less than the above upper limit, the amount of gas generated accompanying the charge-discharge cycle in the non-aqueous electrolyte storage element can be further reduced, and the viscosity of the non-aqueous electrolyte can be reduced. The content of the fluorinated cyclic carbonate in the non-aqueous solvent can be equal to or more than any of the above lower limits and equal to or less than any of the above upper limits.
[0086] The fluorinated chain solvent refers to a compound in which some or all of the hydrogen atoms of the chain solvent are replaced with fluorine atoms. Examples of the fluorinated chain solvent include fluorinated chain hydrocarbons, fluorinated chain ethers, fluorinated chain esters, and fluorinated chain carbonates, among which fluorinated chain carbonates are preferred. The fluorinated chain solvent can be used alone or in combination of two or more.
[0087] Fluorinated linear carbonates are, for example, R a -O-CO-OR b (R a is a fluorinated alkyl group. b is an alkyl group or a fluorinated alkyl group. b is preferably an alkyl group. a and R b Each of these preferably has 1 to 3 carbon atoms, and more preferably 1 or 2 carbon atoms.
[0088] Examples of the fluorinated chain carbonate include fluoromethyl methyl carbonate, fluoroethyl methyl carbonate, difluoroethyl methyl carbonate, trifluoroethyl methyl carbonate, bis(trifluoroethyl)carbonate, methylfluoropropyl carbonate, methyldifluoropropyl carbonate, methyltrifluoropropyl carbonate, methyltetrafluoropropyl carbonate, methylpentafluoropropyl carbonate, bis(trifluoropropyl)carbonate, bis(tetrafluoropropyl)carbonate, bis(pentafluoropropyl)carbonate, etc. Among these, 2,2,2-trifluoroethyl methyl carbonate (TFEMC), which is trifluoroethyl methyl carbonate, is preferred.
[0089] Examples of the fluorinated chain ester include methyl 3,3,3-trifluoropropionate (FMP), 2,2,2-trifluoroethyl acetate (FEA), methyl trifluoroacetate, ethyl trifluoroacetate, 2,2,2-trifluoroethyl trifluoroacetate, methyl 2-fluoropropionate, and ethyl 2-fluoropropionate.
[0090] Examples of fluorinated ethers include 1,1,2,2-tetrafluoro-2,2,2-trifluoroethyl ether (TFEE), 1,1,2,2-tetrafluoroethyl-ethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (HFE), 1,1,2,2-tetrafluoroethyl-2,2,3,3,3-pentafluoropropyl ether, and 1,1,2,2-tetrafluoropropyl-1,1,2,3,3,3-hexafluoropropyl ether.
[0091] The content of the fluorinated chain solvent in the nonaqueous solvent is preferably 20% by volume to 80% by volume, more preferably 50% by volume to 78% by volume, and even more preferably 65% by volume to 75% by volume. By setting the content of the fluorinated chain solvent in the above range, the capacity retention rate after charge-discharge cycles in the nonaqueous electrolyte storage element can be further increased and the amount of gas generated can be further reduced.
[0092] The lower limit of the total content of the fluorinated cyclic carbonate and the fluorinated chain solvent in the non-aqueous solvent is preferably 60% by volume, more preferably 70% by volume, even more preferably 80% by volume, and even more preferably 90% by volume, 95% by volume, or 99% by volume. By making the total content of the fluorinated cyclic carbonate and the fluorinated chain solvent in the non-aqueous solvent equal to or higher than the lower limit, the capacity retention rate after charge-discharge cycles in the non-aqueous electrolyte storage element can be further increased. The upper limit of the total content of the fluorinated cyclic carbonate and the fluorinated chain solvent in the non-aqueous solvent may be 100% by volume.
[0093] The non-aqueous solvent may contain other non-aqueous solvents other than the fluorinated cyclic carbonate and the fluorinated chain solvent. Examples of other non-aqueous solvents include non-fluorinated cyclic carbonates, non-fluorinated chain carbonates, esters other than fluorinated chain esters, and ethers other than fluorinated chain ethers. Examples of non-fluorinated cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinylethylene carbonate (VEC), chloroethylene carbonate, styrene carbonate, 1-phenylvinylene carbonate, and 1,2-diphenylvinylene carbonate. Examples of non-fluorinated chain carbonates include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and diphenyl carbonate.
[0094] The volume ratio of the cyclic solvent to the chain solvent in the non-aqueous solvent (cyclic solvent:chain solvent) is preferably in the range of, for example, 20:80 to 50:50.
[0095] The lower limit of the content of the cyclic carbonate (the total of the fluorinated cyclic carbonate and the non-fluorinated cyclic carbonate) in the cyclic solvent is preferably 60% by volume, more preferably 70% by volume, even more preferably 80% by volume, and even more preferably 90% by volume, 95% by volume, or 99% by volume. By making the content of the cyclic carbonate in the cyclic solvent equal to or higher than the lower limit, the capacity retention rate after the charge-discharge cycle of the non-aqueous electrolyte storage element can be further increased. The upper limit of the content of the cyclic carbonate in the cyclic solvent may be 100% by volume.
[0096] The lower limit of the content of the fluorinated cyclic carbonate in the cyclic carbonate is preferably 60% by volume, more preferably 70% by volume, even more preferably 80% by volume, and even more preferably 90% by volume, 95% by volume, or 99% by volume. By making the content of the fluorinated cyclic carbonate in the cyclic carbonate equal to or higher than the lower limit, the capacity retention rate after the charge-discharge cycle of the non-aqueous electrolyte storage element can be further increased. The upper limit of the content of the fluorinated cyclic carbonate in the cyclic carbonate may be 100% by volume.
[0097] The lower limit of the content of the fluorinated chain solvent in the chain solvent is preferably 60% by volume, more preferably 70% by volume, even more preferably 80% by volume, and even more preferably 90% by volume, 95% by volume or 99% by volume. By making the content of the fluorinated chain solvent in the chain solvent equal to or more than the lower limit, the capacity retention rate after charge / discharge cycles in the nonaqueous electrolyte storage element can be further increased and gas generation can be further reduced. The upper limit of the content of the fluorinated chain solvent in the chain solvent may be 100% by volume.
[0098] The lower limit of the content of carbonate (the total of fluorinated cyclic carbonate, fluorinated chain carbonate and non-fluorinated carbonate) in the non-aqueous solvent is preferably 60% by volume, more preferably 70% by volume, even more preferably 80% by volume, and even more preferably 90% by volume, 95% by volume or 99% by volume. By making the content of carbonate in the non-aqueous solvent equal to or higher than the lower limit, the capacity retention rate after charge-discharge cycles in the non-aqueous electrolyte storage element can be further increased. The upper limit of the content of carbonate in the non-aqueous solvent may be 100% by volume.
[0099] The lower limit of the total content of fluorinated solvents (the total of fluorinated cyclic carbonate, fluorinated chain solvent and other fluorinated solvents) in the non-aqueous solvent is preferably 60% by volume, more preferably 70% by volume, even more preferably 80% by volume, and even more preferably 90% by volume, 95% by volume or 99% by volume. The fluorinated solvent refers to a solvent having elemental fluorine. By making the total content of fluorinated solvents in the non-aqueous solvent equal to or greater than the lower limit, the capacity retention rate after charge-discharge cycles in the non-aqueous electrolyte storage element can be further increased. The upper limit of the total content of fluorinated solvents in the non-aqueous solvent may be 100% by volume.
[0100] By containing a cyclic compound containing a sulfur element in a non-aqueous electrolyte together with a non-aqueous solvent containing a fluorinated cyclic carbonate and a fluorinated chain solvent, it is possible to achieve both a high capacity retention rate after charge / discharge cycles and suppression of gas generation in a non-aqueous electrolyte storage element having a negative electrode using a silicon-based active material. The cyclic compound containing a sulfur element is usually an organic compound. The cyclic compound containing a sulfur element is preferably a compound having a heterocyclic structure containing a sulfur element. Examples of the cyclic compound containing a sulfur element include compounds having a cyclic sulfate structure, a sultone structure, a cyclic sulfone structure, a cyclic sulfite structure, a cyclic sulfoxide structure, a cyclic sulfide structure, and the like. One or more types of cyclic compounds containing a sulfur element can be used.
[0101] A compound having a cyclic sulfate structure refers to a compound containing a ring structure in which two carbon atoms are each bonded to an oxysulfonyloxy group (-OS(=O)2-O-). Specific examples of compounds having a cyclic sulfate structure include ethylene sulfate, 1,3-propylene sulfate, 2,3-propylene sulfate, 4,5-pentene sulfate, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, etc.
[0102] A compound having a sultone structure refers to a compound containing a ring structure in which two carbon atoms are each bonded to a sulfonyloxy group (-S(=O)2O-). A compound having a sultone structure is a type of cyclic sulfonate ester, and the cyclic compound containing a sulfur element may be a cyclic sulfonate ester, but a compound having a sultone structure is preferred. Specific examples of the compound having a sultone structure include 1,3-propane sultone, 1,4-butane sultone, 1,3-propene sultone, 1-methyl-1,3-propene sultone, 2-methyl-1,3-propene sultone, 3-methyl-1,3-propene sultone, and 1,4-butene sultone, and specific examples of cyclic sulfonate esters other than the compound having a sultone structure include methylenemethane disulfonate.
[0103] A compound having a cyclic sulfone structure refers to a compound containing a ring structure in which two carbon atoms are each bonded to a sulfonyl group (-S(=O)2-). Specific examples of compounds having a cyclic sulfone structure include sulfolane, 3-methylsulfolane, 3-sulfolene, 1,1-dioxothiophene, 3-methyl-2,5-dihydrothiophene-1,1-dioxide, and methyl 3-sulfolene-3-carboxylate.
[0104] A compound having a cyclic sulfite structure refers to a compound containing a ring structure in which two carbon atoms are each bonded to an oxysulfinyloxy group (-OS(=O)-O-). Specific examples of compounds having a cyclic sulfite structure include ethylene sulfite, 1,2-propylene glycol sulfite, trimethylene sulfite, and 1,3-butylene glycol sulfite.
[0105] A compound having a cyclic sulfoxide structure refers to a compound containing a ring structure in which two carbon atoms are each bonded to a sulfinyl group (-S(=O)-). A specific example of a compound having a cyclic sulfoxide structure is tetramethylene sulfoxide.
[0106] A compound having a cyclic sulfide structure refers to a compound containing a ring structure in which two carbon atoms are each bonded to a divalent sulfur (-S-). Specific examples of compounds having a cyclic sulfide structure include tetrahydrothiophene, thiophene, thiane, 1,3-dithiane, 5,6-dihydro-1,4-dithiine-2,3-dicarboxylic anhydride, and 3,4-thiophenedicarboxylic anhydride.
[0107] As the cyclic compound containing elemental sulfur, a compound having a ring structure containing a sulfonyl group (-S(=O)2-) is preferred. Such compounds include the above-mentioned compounds having a cyclic sulfate structure, a sultone structure, a cyclic sulfone structure, and the like. Furthermore, as the cyclic compound containing elemental sulfur, a compound having a cyclic sulfate structure or a cyclic sulfonate ester is preferred, a compound having a sultone structure is more preferred, and a compound having a carbon-carbon double bond and a sultone structure is even more preferred. When the cyclic compound containing elemental sulfur is such a compound, the capacity retention rate after charge-discharge cycles in the nonaqueous electrolyte storage element can be further increased and gas generation can be further reduced.
[0108] In addition, as the cyclic compound containing sulfur element, a compound having a carbon-carbon double bond is also preferred, a compound having a carbon-carbon double bond in a heterocyclic structure containing sulfur element is more preferred, and a compound having a carbon-carbon double bond in a sultone structure is even more preferred.When the cyclic compound containing sulfur element is such a compound, the capacity retention rate after charge-discharge cycles in the non-aqueous electrolyte storage element can be further increased and gas generation can be further reduced.Such suitable compounds include 1,3-propene sultone, 1-methyl-1,3-propene sultone, 2-methyl-1,3-propene sultone, 3-methyl-1,3-propene sultone, 1,4-butene sultone, etc., as exemplified above, and 1,3-propene sultone is particularly preferred.
[0109] The sulfur-containing cyclic compound may be a compound composed of carbon, hydrogen, sulfur and oxygen elements.
[0110] The lower limit of the content of the cyclic compound containing elemental sulfur in the non-aqueous electrolyte is preferably 0.01% by mass, more preferably 0.1% by mass, more preferably 0.5% by mass, even more preferably 1% by mass, and even more preferably 2% by mass, 3% by mass, or 4% by mass. By making the content of the cyclic compound containing elemental sulfur equal to or more than the above lower limit, the generation of gas after charge-discharge cycles in the non-aqueous electrolyte storage element can be further suppressed. On the other hand, the upper limit of the content of the cyclic compound containing elemental sulfur in the non-aqueous electrolyte is 18% by mass, preferably 15% by mass, more preferably 12% by mass, even more preferably 10% by mass, even more preferably 8% by mass, and even more preferably 6% by mass, 4% by mass, 3% by mass, or 2% by mass. By making the content of the cyclic compound containing elemental sulfur equal to or less than the above upper limit, the capacity retention rate after charge-discharge cycles in the non-aqueous electrolyte storage element can be further increased. The content of the cyclic compound containing elemental sulfur in the non-aqueous electrolyte can be equal to or more than any of the above lower limits and equal to or less than any of the above upper limits.
[0111] The non-aqueous electrolyte may contain other additives in addition to the electrolyte salt, the non-aqueous solvent, and the cyclic compound containing elemental sulfur. Examples of the other additives include aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; and halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole. ; succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, cyclohexanedicarboxylic anhydride; dimethyl sulfite, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, diphenyl sulfide, thioanisole, diphenyl disulfide, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, etc. These other additives may be used alone or in combination of two or more.
[0112] The content of other additives contained in the non-aqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By setting the content of the additives within the above range, it is possible to improve the capacity retention performance or cycle performance after high-temperature storage, and to further improve safety.
[0113] In one embodiment of the present invention, the nonaqueous electrolyte may be a nonaqueous electrolyte solution. The nonaqueous electrolyte solution is a liquid nonaqueous electrolyte having fluidity at, for example, 20°C. The lower limit of the total content of the electrolyte salt, the nonaqueous solvent, and the cyclic compound containing elemental sulfur in the nonaqueous electrolyte may be 60 mass%, 70 mass%, 80 mass%, 90 mass%, or 95 mass%. The upper limit of the total content may be 100 mass%. The nonaqueous electrolyte may further include a solid electrolyte, a polymer, or the like. In one embodiment of the present invention, the nonaqueous electrolyte may be a gel electrolyte.
[0114] (shape, etc.) The shape of the nonaqueous electrolyte storage element of this embodiment is not particularly limited, and examples thereof include a cylindrical battery, a prismatic battery, a flat battery, a coin battery, and a button battery.
[0115] Fig. 1 shows a nonaqueous electrolyte storage element 1 as an example of a prismatic battery. The figure is a see-through view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a prismatic container 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51.
[0116] The lower limit of the energy density per mass of the nonaqueous electrolyte storage element of this embodiment during normal use is preferably 350Wh / kg, more preferably 380Wh / kg, and even more preferably 400Wh / kg. The nonaqueous electrolyte storage element is preferably used in such a form having high energy density. The upper limit of the energy density may be 600Wh / kg, 500Wh / kg, or 450Wh / kg. The energy density may be equal to or greater than any of the lower limits and equal to or less than any of the upper limits. In specifying the energy density and the discharge capacity described below, if the discharge current during normal use is not determined, the value is taken as the value when the discharge current is 0.1C.
[0117] The discharge capacity per area of the positive electrode active material layer during normal use of the nonaqueous electrolyte storage element of this embodiment is 7 mAh / cm 2 More than 18mAh / cm 2 Less than 8mAh / cm is preferred 2 More than 15mAh / cm 2 Less than 8.5mAh / cm is more preferable. 2 More than 12mAh / cm 2 The following is even more preferable: When the discharge capacity per area of the positive electrode active material layer is within the above range, the energy density per mass of the nonaqueous electrolyte storage element can be further increased.
[0118] The lower limit of the charge cut-off voltage during normal use of the nonaqueous electrolyte storage element of this embodiment is preferably 4.30V, more preferably 4.50V, and even more preferably 4.55V. When the charge cut-off voltage is equal to or higher than the lower limit, the energy density per mass of the nonaqueous electrolyte storage element can be further increased. The upper limit of the charge cut-off voltage may be 4.80V, 4.75V, 4.70V, or 4.65V. The charge cut-off voltage may be equal to or higher than any of the lower limits and equal to or lower than any of the upper limits.
[0119] <Electricity storage device> The nonaqueous electrolyte storage element of the present embodiment can be mounted as an electricity storage unit (battery module) comprising a plurality of nonaqueous electrolyte storage elements assembled together in automobile power sources such as electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc., power sources for electronic devices such as personal computers and communication terminals, or power storage power sources, etc. In this case, the technology of the present invention may be applied to at least one of the nonaqueous electrolyte storage elements included in the electricity storage unit.
[0120] 2 shows an example of an electricity storage device 30 in which electricity storage units 20, each of which is an assembly of two or more electrically connected nonaqueous electrolyte electricity storage elements 1, are further assembled. The electricity storage device 30 may include a bus bar (not shown) that electrically connects the two or more nonaqueous electrolyte electricity storage elements, a bus bar (not shown) that electrically connects the two or more electricity storage units 20, and the like. The electricity storage unit 20 or the electricity storage device 30 may include a status monitoring device (not shown) that monitors the status of the one or more nonaqueous electrolyte electricity storage elements.
[0121] <Method of Manufacturing Nonaqueous Electrolyte Storage Element> The method for producing the nonaqueous electrolyte storage element of the present embodiment can be appropriately selected from known methods. The method for producing the nonaqueous electrolyte storage element of the present embodiment includes, for example, preparing an electrode body, preparing a nonaqueous electrolyte, and housing the electrode body and the nonaqueous electrolyte in a container. The preparation of the electrode body includes preparing a positive electrode and a negative electrode, and forming the electrode body by stacking or rolling the positive electrode and the negative electrode with a separator interposed therebetween.
[0122] The method of housing the non-aqueous electrolyte in the container can be appropriately selected from known methods. For example, when a non-aqueous electrolyte solution is used as the non-aqueous electrolyte, the non-aqueous electrolyte solution may be injected through an injection port formed in the container, and then the injection port may be sealed.
[0123] <Other embodiments> The nonaqueous electrolyte storage element of the present invention is not limited to the above-described embodiment, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.
[0124] In the above embodiment, the nonaqueous electrolyte storage element is used as a chargeable and dischargeable nonaqueous electrolyte secondary battery (lithium ion secondary battery), but the type, shape, size, capacity, etc. of the nonaqueous electrolyte storage element are arbitrary. The present invention can be applied to various secondary batteries.
[0125] In the above embodiment, the electrode assembly in which the positive electrode and the negative electrode are stacked with a separator interposed therebetween has been described, but the electrode assembly may not include a separator. For example, the positive electrode and the negative electrode may be in direct contact with each other in a state in which a non-conductive layer is formed on the active material layer of the positive electrode or the negative electrode. EXAMPLES
[0126] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0127] The positive electrode active materials and negative electrode active materials used in the examples and comparative examples are shown below. (Cathode active material) NCM622: LiNi with α-NaFeO2 type crystal structure 0.6 Co 0.2 Mn 0.2 O2 NCM523: LiNi with α-NaFeO2 type crystal structure 0.5 Co 0.2 Mn 0.3 O2 (Negative electrode active material) SiO: Silicon oxide (SiO), a silicon-based active material Gr: Graphite
[0128] [Example 1] (Preparation of positive electrode) A positive electrode mixture paste was prepared containing NCM622 as a positive electrode active material, acetylene black (AB) and single-walled carbon nanotubes (SWCNT) as conductive agents, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a dispersion medium. The mass ratio of the positive electrode active material, AB, SWCNT, and binder was 98.52:0.40:0.08:1.00 in terms of solid content. The positive electrode mixture paste was applied to one side of an aluminum foil having an average thickness of 15 μm as a positive electrode substrate, dried, and pressed to form a positive electrode active material layer. As a result, a positive electrode in which a positive electrode active material layer was laminated on a positive electrode substrate was obtained. The mass per area of the positive electrode active material layer was 4.5 g / 100 cm2 , the porosity was 25%.
[0129] (Preparation of negative electrode) Silicon oxide (SiO) doped with lithium element in advance was used as the negative electrode active material. A negative electrode mixture paste was prepared containing the above-mentioned negative electrode active material, single-walled carbon nanotubes (SWCNT) as a conductive agent, styrene butadiene rubber (SBR) as a binder, carboxymethyl cellulose (CMC) as a thickener, and water as a dispersion medium. The mass ratio of the negative electrode active material, the conductive agent, the binder, and the thickener was 89.7:0.3:8.8:1.2 in terms of solid content. The negative electrode mixture paste was applied to one side of a copper foil having an average thickness of 6 μm as a negative electrode substrate, dried, and pressed to form a negative electrode active material layer. As a result, a negative electrode in which a negative electrode active material layer was laminated on a negative electrode substrate was obtained. The mass per area of the negative electrode active material layer was 0.81 g / 100 cm 2 It was.
[0130] (Preparation of non-aqueous electrolyte) A non-aqueous solvent consisting of a mixture of fluoroethylene carbonate (FEC) and 2,2,2-trifluoroethyl methyl carbonate (TFEMC) in a volume ratio of 30:70 was added to the lithium salt LiPF6 at a concentration of 1.6 mol / dm 3 In the obtained solution, 1,3-propene sultone (PRS) was dissolved in a content of 2 mass % to prepare a non-aqueous electrolyte.
[0131] (Assembly of non-aqueous electrolyte storage element) The positive electrode and the negative electrode were laminated with a polyethylene microporous membrane separator interposed therebetween to prepare an electrode assembly. The electrode assembly was placed in a container made of a metal resin composite film, and the nonaqueous electrolyte was poured into the container, which was then sealed by heat welding to obtain the nonaqueous electrolyte storage element of Example 1.
[0132] [Examples 2 to 8, Comparative Examples 1 to 10] Each of the nonaqueous electrolyte storage elements of Examples 2 to 8 and Comparative Examples 1 to 10 was obtained in the same manner as in Example 1, except that the type of positive electrode active material, the mass per area of the positive electrode active material layer, the type of negative electrode active material, the mass per area of the negative electrode active material layer, the type of nonaqueous solvent, the volume ratio of the nonaqueous solvent, and the content of 1,3-propene sultone (PRS) were as shown in Table 1. In Table 1, "-" means that 1,3-propene sultone (PRS) was not contained. In addition, when the negative electrode active material was graphite (Gr), a negative electrode prepared by the following method was used. A negative electrode mixture paste was prepared containing graphite (Gr) as the negative electrode active material, SBR as the binder, CMC as the thickener, and water as the dispersion medium. The mass ratio of the negative electrode active material, the binder, and the thickener was 96.7:2.1:1.2 in terms of solid content. The negative electrode mixture paste was applied to one side of copper foil as the negative electrode substrate, dried, and pressed to form a negative electrode active material layer. As a result, a negative electrode in which a negative electrode active material layer was laminated on the negative electrode substrate was obtained.
[0133] [evaluation] (Chemical) The nonaqueous electrolyte storage elements of Examples 1 to 8 and Comparative Examples 1 to 10 thus assembled were subjected to the following chemical formation. Constant current charging was performed at 25°C, with a charging current of 0.05C and a charging time of 6 hours. A rest period of 48 hours was then provided. Next, constant current / constant voltage charging was performed with a charging current of 0.05C and a charge cut-off voltage shown in Table 1. The charge cut-off condition was the time when the charging current attenuated to 0.04C. Next, constant current discharging was performed with a discharging current of 0.1C and a discharge cut-off voltage shown in Table 1. A rest period of 10 minutes was provided after each charging and discharging. In addition, it was confirmed by EDX analysis that each of the nonaqueous electrolyte storage elements of Examples 1 to 8 and Comparative Examples 2, 4 to 6, and 8 to 10, which had a nonaqueous electrolyte containing 1,3-propene sultone (PRS), had sulfur element originating from the coating film that accompanies charging and discharging on at least a part of the surface of the negative electrode after chemical formation. (Initial charge / discharge) The nonaqueous electrolyte storage elements of Examples 1 to 8 and Comparative Examples 1 to 10 after formation were subjected to the following initial charge and discharge. Constant-current constant-voltage charging was performed at 25°C with a charging current of 0.2C and a charge cut-off voltage shown in Table 1. The charge cut-off condition was the time when the charging current attenuated to 0.05C. Next, constant-current discharging was performed with a discharging current of 0.1C and a discharge cut-off voltage shown in Table 1. A rest period of 10 minutes was provided after each charge and discharge.
[0134] (energy density) The energy density (energy density per mass of the nonaqueous electrolyte electricity storage element) was calculated based on the discharge capacity in the above initial charge and discharge. The results are shown in Table 1.
[0135] (Charge-discharge cycle test) A charge-discharge cycle test was carried out on each of the nonaqueous electrolyte storage elements of Examples 1 to 8 and Comparative Examples 1 to 10, which had been subjected to the above initial charge-discharge, in the following manner. Constant-current constant-voltage charging was carried out at 25°C, a charging current of 0.2C, and a charge cut-off voltage shown in Table 1. The charge cut-off condition was the time when the charging current attenuated to 0.05C. Thereafter, constant-current discharging was carried out at a discharge current of 0.33C and a discharge cut-off voltage shown in Table 1. A rest period of 10 minutes was provided after each charge and discharge. This charge-discharge cycle was carried out 100 times.
[0136] (Capacity maintenance rate) After the charge-discharge cycle test was performed 100 times, the nonaqueous electrolyte storage elements of Examples 1 to 8 and Comparative Examples 1 to 10 were charged and discharged under the same conditions as the initial charge-discharge test, and the discharge capacity after 100 cycles was measured. The percentage of the discharge capacity after 100 cycles to the discharge capacity in the initial charge-discharge test was calculated as the capacity retention rate. The results are shown in Table 1.
[0137] (Gas generation rate) The amount of gas generated in the charge-discharge cycle test was determined for each of the nonaqueous electrolyte storage elements of Examples 1 to 7 and Comparative Examples 1 to 9. Specifically, the volume (V1) of the nonaqueous electrolyte storage element after the initial charge-discharge and the volume (V2) of the nonaqueous electrolyte storage element after the charge-discharge cycle test were measured by Archimedes' method, and the amount of gas generated was calculated by determining the difference in volume (V2-V1). The results are shown in Table 1. Note that the amount of gas generated was not determined for each of the nonaqueous electrolyte storage elements of Example 8 and Comparative Example 10.
[0138] [Table 1]
[0139] The results in Table 1 reveal the following: The nonaqueous electrolyte storage elements of Comparative Examples 1 and 2, which used graphite (Gr) as the negative electrode active material, had low energy density and capacity retention per mass. On the other hand, Comparative Example 3, which used a silicon-based active material as the negative electrode active material but did not contain 1,3-propene sultone (PRS) in the nonaqueous electrolyte, generated a large amount of gas and also did not have a high capacity retention. Comparative Example 4, in which the content of 1,3-propene sultone (PRS) in the nonaqueous electrolyte was more than 18 mass%, and Comparative Examples 5 and 6, in which the content of fluoroethylene carbonate (FEC) in the nonaqueous solvent was less than 20 volume%, were able to suppress gas generation but had low capacity retention. The mass per area of the positive electrode active material layer was 3.5 g / 100 cm 2 The capacity retention rate was low in Comparative Examples 7 to 9, in which the non-aqueous solvent did not contain a fluorinated chain solvent, and the energy density per mass was low.
[0140] In contrast, the positive electrode active material layer is mainly composed of a lithium transition metal composite oxide having an α-NaFeO2 type crystal structure, and the mass per area of the positive electrode active material layer is 3.5 g / 100 cm 2 More than 10.5g / 100cm 2The nonaqueous electrolyte storage elements of Examples 1 to 8, in which the negative electrode has sulfur element at least on a part of the surface, the negative electrode active material layer is mainly composed of a silicon-based active material, the content of PRS, which is a cyclic compound containing the above-mentioned sulfur element, in the nonaqueous electrolyte is 18 mass% or less, the nonaqueous solvent contains FEC, which is a fluorinated cyclic carbonate, and TFEMC, which is a fluorinated chain solvent, and the content of FEC, which is a fluorinated cyclic carbonate, in the nonaqueous solvent is 20 volume% or more, had high capacity retention rate, energy density, and small gas generation amount. Also, compared with Examples 1 to 3, there was a tendency that the amount of gas generation was reduced by increasing the concentration of the cyclic compound containing the sulfur element.
[0141] From the above results, the nonaqueous electrolyte storage elements of the respective Examples have high energy densities suited to various applications and are useful as nonaqueous electrolyte storage elements with little decrease in the amount of gas generated and in the discharge capacity retention rate. [Industrial Applicability]
[0142] The present invention can be applied to nonaqueous electrolyte electricity storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles. [Explanation of symbols]
[0143] 1. Non-aqueous electrolyte storage element 2 Electrode body 3 containers 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device
Claims
1. The battery includes a positive electrode having a positive electrode active material layer, a negative electrode having a negative electrode active material layer, and a non-aqueous electrolyte having a non-aqueous solvent and a cyclic compound containing elemental sulfur; The positive electrode active material layer is α-NaFeO 2 The main component is a lithium transition metal composite oxide having a type crystal structure, The mass per area of the positive electrode active material layer is 3.5 g / 100 cm 2 More than 10.5g / 100cm 2 is as follows: The negative electrode has elemental sulfur on at least a portion of its surface, The negative electrode active material layer contains a silicon-based active material as a main component, the content of the cyclic compound containing elemental sulfur in the nonaqueous electrolyte is 18% by mass or less, the non-aqueous solvent contains a fluorinated cyclic carbonate and a fluorinated chain solvent, A nonaqueous electrolyte electricity storage element, wherein the content of the fluorinated cyclic carbonate in the nonaqueous solvent is 20% by volume or more.
2. 2. The nonaqueous electrolyte storage element according to claim 1, wherein the porosity of the positive electrode active material layer is 15% or more and 35% or less.
3. 3. The nonaqueous electrolyte storage element according to claim 1, wherein the cyclic compound containing elemental sulfur includes at least one selected from a compound having a cyclic sulfate structure and a cyclic sulfonate ester.
4. 4. The nonaqueous electrolyte electricity storage element according to claim 3, wherein the cyclic compound containing elemental sulfur has a sultone structure.
5. 3. The nonaqueous electrolyte storage element according to claim 1, wherein the cyclic compound containing elemental sulfur has a carbon-carbon double bond.
Citation Information
Patent Citations
Composite particle and manufacturing method therefor as well as negative electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte battery using the negative electrode
JP2004356078A
Nonaqueous secondary battery
JP2010212228A
Positive electrode active material for lithium secondary battery, positive electrode and secondary battery
JP2015018678A
Nonaqueous electrolytic secondary battery
JP2015053152A